Quantitative Hemodynamic Analysis of Brain Aneurysms at Different Locations - Chien, A. (AJNR Am J Neuroradiol, 2009)
BACKGROUND AND PURPOSE: Studies have shown that the occurrence of brain aneurysms and risk of rupture vary between locations. However, the reason that aneurysms at different branches of the cerebral arteries have different clinical presentations is not clear. Because research has indicated that aneurysm hemodynamics may be one of the important factors related to aneurysm growth and rupture, our aim was to analyze and compare the flow parameters in aneurysms at different locations. MATERIALS AND METHODS: A total of 24 patient-specific aneurysm models were constructed by using 3D rotational angiographic data for the hemodynamic simulation. Previously developed computational fluid dynamics software was applied to each aneurysm to simulate the blood-flow properties. Hemodynamic data at peak pulsatile flow were recorded, and wall shear stress (WSS) and flow rate in the aneurysms and parent arteries were quantitatively compared. To validate our method, a comparison with a previously reported technique was also performed. RESULTS: WSS and flow rate in the aneurysms at the peak of the cardiac cycle were found to differ in magnitude between different locations. Multiple comparisons among locations showed higher WSS and flow rate in middle cerebral artery aneurysms and lower WSS and flow rate in basilar artery and anterior communicating artery aneurysms. CONCLUSIONS: We observed changes in hemodynamic values that may be related to aneurysm location. Further study of aneurysm locations with a large number of cases is needed to test this hypothesis.